FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN PENGEMUDI BUS DI CV. MAKMUR MEDAN TAHUN 2014 - meutia siregar; makmur sinaga; umi salmah (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT This research was conducted on driver 1 of CV. Makmur heading for Pekan Baru from Medan (round trip) in 2014 in order to find out some factors which were correlated with the incidence of fatigue. The research was an analytic survey with cross sectional design which was aimed to find out the correlation of the factors of age, driving duration, physical condition, break time, and nutrition/IMT status with the incidence of fatigue. The population was 160 drivers, and 32 of them were used as the samples, taken by using purposive sampling technique with the most frequent departure was 8 buses heading for Pekan Baru from Medan (round trip) each day. Drivers’ fatigue was measured from the round trip transportation line, using questionnaires on fatigue subjectively with the scale of Industrial Fatigue Research Committee (IFRC) which was categorized from the level of not tired, rather tired, moderately tired, and very tired. Chi square statistic test was used to find out the correlation between independent variables and dependent variable. Based on the distribution frequency, it was found that 13 respondents (40.6%) were rather tired, 11 respondents (34.4%) were moderately tired, and 8 respondents (25%) were very tired. The result of chi square test showed that   there was significant correlation between age and the incidence of fatigue at p-value = 0.012 (p < 0.05), between driving duration of departure and fatigue at p-value = 0.016, between driving duration of return and fatigue at p-value = 0.036, between break time of departure and fatigue at p-value = 0.006, between break time of return and fatigue at p-value = 0.016, and between nutrition/IMT status and fatigue at p-value = 0.016. Meanwhile, there was insignificant correlation between physical condition and the incidence of fatigue. It is suggested that tired drivers should decrease their stamina and increase the risk for accident. Motorists who have above-normal weight or obese should reduce smoking, drinking coffee or drinks stamina for the driver awake and avoid health problems. Drivers who are above 40 years old or more should pay their attention to their rest; when they feel very sleepy, they should change place with drivers 2 in order to get fresh  and increase oxygen content in blood so that they will be refreshed.